The effects of valsartan on cognitive deficits induced by aluminum trichloride and d-galactose in mice. (July 2014) - Yang, Wei-Na; Hu, Xiao-Dan; Han, Hua; Shi, Li-Li; Feng, Gai-Feng; Liu, Yong; Qian, Yi-Hua
Abstract : Objectives: Valsartan has been reported to reduce brain beta-amyloid protein levels and improve spatial learning in the Tg2576 transgenic mouse model of Alzheimer's disease (AD). However, the exact mechanism of neuroprotective effects of valsartan has not been properly studied especially in cholinergic function and oxidative damage, the essential factors that undergo impairment in AD. Therefore, the present study examined the effects of valsartan on memory impairment, cholinergic dysfunction, and oxidative stress in aluminum trichloride (AlCl3 ) andd -galactose (d -gal)-induced experimental sporadic dementia of Alzheimer's type. Methods: Valsartan was administered intragastrically (i.g.) (20 mg/kg/day) for 60 days after mice were given AlCl3 (10 mg/kg/day) andd -gal (150 mg/kg/day) intraperitoneally (i.p.) once daily for 90 days. Then, memory function was evaluated by Morris water maze test. Acetylcholinesterase (AChE), superoxide dismutases (SOD) and glutathione peroxidase (GSH-Px) activities and malondialdehyde (MDA) level in cortex and hippocampus were also assessed with biochemical technique. Results: Chronic administration of valsartan not only improved learning and memory but also restored the elevation of AChE activity induced by AlCl3 andd -gal in cortex and hippocampus. In addition, valsartan significantly restored SOD and GSH-Px activities and reduced MDA level in cortex and hippocampus indicating attenuation of oxidative stress. Discussion: Our results indicate that valsartan prevents AlCl3 - andd -gal-induced cognitive decline partly to restore cholinergic function and attenuate oxidative damage. These findings further support the potential of valsartan to be used in AD treatment.